2011
DOI: 10.1007/s10876-011-0395-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Hydrogen Adsorption on Ruthenium Clusters

Abstract: The geometries, stabilities, electronic, and magnetic properties of hydrogen adsorption on Ru n clusters have been systematically investigated by using density functional theory with generalized gradient approximation. The result indicates the absorbed species does not lead to a rearrangement of the basic cluster. For n [ 2, three different adsorption patterns are found for the Ru n H 2 complexes: One H atom binds to the Ru top site, and another H binds to the bridge site for n = 3, 5, 6, 8; bridge site adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
(48 reference statements)
1
13
0
1
Order By: Relevance
“…1 However, the ground state structure of Ru 2 in this work is 1.14 eV lower than previous work where H atoms are adsorbed on top of one Ru atom. 21 The Ru-H distance in Ru 2 , Ru 4 , and Ru 7 is calculated to be 1.61Å, 1.61Å, and 1.68 A, respectively, while H 2 adsorption energy on Ru 7 is higher than Ru 2 and Ru 4 . H atoms are adsorbed on the top and bridge sites of Ru atoms in Ru 3 , Ru 6 , and Ru 8 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…1 However, the ground state structure of Ru 2 in this work is 1.14 eV lower than previous work where H atoms are adsorbed on top of one Ru atom. 21 The Ru-H distance in Ru 2 , Ru 4 , and Ru 7 is calculated to be 1.61Å, 1.61Å, and 1.68 A, respectively, while H 2 adsorption energy on Ru 7 is higher than Ru 2 and Ru 4 . H atoms are adsorbed on the top and bridge sites of Ru atoms in Ru 3 , Ru 6 , and Ru 8 .…”
Section: Resultsmentioning
confidence: 93%
“…Aer Ru 4 , bare Ru clusters are more stable than H 2 adsorbed Ru clusters conrming the nding of previously reported results. 21 For the Os cases, the threshold of the stability change is the size of 3. A possible explanation of the stability change can be explained by the strength of H and Fe, Ru, and Os.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FeRu solid solution exhibited a positive H 2 reaction order, attributed to a reduced overlap of Ru d-states with the s-states from H compared to pristine Ru(0001) [15]. Theoretically, the H atom binding [15][16][17] and its diffusion [18,19] on Ru surfaces and the H 2 dissociative adsorption on Ru nanoparticles [20][21][22] were studied extensively. Modulation-excitation infrared spectroscopy (MEIRS) measurements together with density functional theory (DFT) calculations revealed that the dissociation of activated H 2 molecules is more probable than their adsorption, leading to the hydrogenation of the surface of the Ru catalyst [23].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Structurally, DFT-based calculations have shown that small Ru N clusters prefer to adopt cubic-like structures. [20][21][22][23] Sn N clusters have attracted attention mainly because of remarkable thermal properties; the melting temperature for small clusters appears to be higher than that of the bulk. 24 Regarding their structure, a transition from planar to 3D geometries occurs at Sn 4 (rhombohedral) to Sn 5 (trigonal bipyramid), whereas larger clusters tend to form prolate-like open structures.…”
Section: Introductionmentioning
confidence: 99%